Social evil threatens the integral development of the human person and of the human society - Migles, Silvija (2018)
This paper discusses social evil as one type of various forms of evil. That is, the Social Doctrine of the Catholic Church offers much scope for theological reflection on evil as a social phenomenon. It provides a socio-ethical perspective within which we can reflect on the reality of evil and its manifestations in the human society. The first part discusses the phenomenon of social evil and a plausible description of its essence in the context of deprivation and threats it poses to the integral human development in society. The second part points out the specific forms of social evil in the present day that threaten human dignity and prevent »full development of the whole man and of all men« (Sollicitudo rei socialis, no. 38; Populorum progressio, no. 42). Certain forms of social evil are increasingly multiplying and becoming a serious obstacle to the integral development of the human person and of the human society. Finally, the question of human freedom arises that reaches its full realization in the choice of good, which confirms the quality of existence. As true human existence cannot be thought of without its spiritual dimension that opens towards the Absolut, the path towards the full development of the whole person, of each individual and of the human society depends on the urgent need for value options.
Među različitim vrstama zla postoji i socijalno zlo o kojem se raspravlja u ovom prilogu. Naime, socijalni nauk Katoličke crkve omogućuje teološku refleksiju o zlu kao socijalnom fenomenu. Riječ je o socijalno-etičkoj perspektivi unutar koje se želi promišljati stvarnost zla i njegove manifestacije u ljudskom društvu. U prvom dijelu raspravlja se o fenomenu socijalnog zla i određenju njegove biti te ga se smješta u kontekst lišavanja i ugrožavanja integralnog ljudskog razvoja u društvu. U drugom dijelu ukazuje se na oblike socijalnog zla u današnjem vremenu kojima se ugrožava ljudsko dostojanstvo i priječi »puni razvoj čitava čovjeka i svih ljudi« (Populorum progressio, br. 42; Sollicitudo rei socialis, br. 38;). Naime, oblici socijalnog zla sve se više umnažaju i tako postaju ozbiljnom zaprekom integralnog razvoja čovjeka i ljudskog društva. Na kraju stoji pitanje ljudske slobode koja svoje puno ostvarenje dosiže u izboru dobra kojim se potvrđuje kvaliteta postojanja. Budući da se istinsko ljudsko postojanje ne da misliti bez njegove »duhovne« dimenzije koja ga otvara prema Apsolutnome (usp. Populorum progressio, br. 42), hod prema punom razvoju čitavog čovjeka, svakog čovjeka i ljudskog društva ovisi o hitnoj potrebi vrijednosnih opredjeljenja.
Societas Ethica’s 54th Annual Conference, Melissatika Volos, 24.-27.8. 2017.
Bilješke uz tekst.
Bibliografske bilješke uz tekst.
Summary ; Sažetak.
Keywords: Ljudsko društvo -- Vrednote -- Socijalno zlo -- Socijalni nauk Crkve -- Crkva